2012
DOI: 10.1074/jbc.m112.347278
|View full text |Cite
|
Sign up to set email alerts
|

Specific Domains in Yeast Translation Initiation Factor eIF4G Strongly Bias RNA Unwinding Activity of the eIF4F Complex toward Duplexes with 5′-Overhangs

Abstract: Background:In yeast, eIF4A and eIF4F are essential for efficient translation initiation, but our understanding of their mechanisms of action is rudimentary. Results: A detailed biochemical analysis of yeast eIF4A, alone and within eIF4F, is described. Conclusion: The eIF4G subunit confers specificity for unwinding duplexes with 5Ј-overhangs on yeast eIF4F. Significance: The observed 5Ј-end specificity may play a role in ribosomal scanning along mRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
62
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 42 publications
20
62
2
Order By: Relevance
“…This RNA, consisting of a 9 base-pair duplex region adjacent to hairpin 92 of 23S rRNA, has previously been used in unwinding 9,27,28 and single-molecule FRET experiments., 9,13 RNA unwinding was followed by a decrease in acceptor (Cy5) fluorescence. In agreement with previous studies eIF4A showed very low intrinsic helicase activity 6,9,11,18,[24][25][26] and unwound the 32/9mer with a rate constant of k unwind D 0.08 ( §0.06) £ 10 ¡3 s ¡1 (Fig. 4 C,D).…”
Section: Atp Analogsupporting
confidence: 92%
“…This RNA, consisting of a 9 base-pair duplex region adjacent to hairpin 92 of 23S rRNA, has previously been used in unwinding 9,27,28 and single-molecule FRET experiments., 9,13 RNA unwinding was followed by a decrease in acceptor (Cy5) fluorescence. In agreement with previous studies eIF4A showed very low intrinsic helicase activity 6,9,11,18,[24][25][26] and unwound the 32/9mer with a rate constant of k unwind D 0.08 ( §0.06) £ 10 ¡3 s ¡1 (Fig. 4 C,D).…”
Section: Atp Analogsupporting
confidence: 92%
“…Similar conformational changes have been previously observed on binding of eIF4G to eIF4A (28,73), and they have also been described for the SF1 helicase Upf1 up on binding of its cofactor Upf2 (74). In these cases, it remains to be seen if these changes affect the RNAbinding specificity, even though the interaction with eIF4G increases specificity for unwinding of helices with a 5′-overhang by eIF4A (75). This role of cofactors in improving the specificity of DEAD-box proteins via allosteric changes in the DEAD-box proteins augments the previously postulated role of recruitment of helicases to their substrates, which requires the prebinding of the cofactor to its substrate via RNA binding, or in the case of Nup159, via binding to the correct position on the nuclear pore.…”
Section: Discussionsupporting
confidence: 72%
“…The absence of yeIF4B in a tif3Δ mutant extract confers cold-sensitive translation in a manner rescued by mammalian eIF4B, indicating that the yeast and mammalian proteins share a conserved critical function. Surprisingly, however, yeIF4B does not stimulate the helicase activity of eIF4A in vitro (Altmann et al 1995;Rajagopal et al 2012), and consistent with this, the C-terminal domain (CTD) (Fig. 1A,B) of yeIF4B shows no obvious similarity to that of mammalian eIF4B (Altmann et al 1993;Coppolecchia et al 1993).…”
Section: Introductionsupporting
confidence: 58%